A Holy Exchange: The Dedicatory Epistle of Clément Marot’s Translation of the Psalms - Haake, Gregory P. (Renaissance and Reformation / Renaissance et Réforme, 2019)
Clément Marot, poet and evangelical sympathizer, published his own translation of thirty psalms in 1541, which in itself was not remarkable at the time. However, what distinguishes this collection is the dedicatory epistle that precedes it. Marot does more than flatter the king, to whom he dedicates his work, or introduce the text that follows. In this article, I argue that Marot composes a dedicatory epistle that, while following contemporary conventions of the genre, takes advantage of those conventions to accomplish a specific evangelical goal in a complex and sensitive religious and political environment. The text creates a typical exchange between patron and poet—the patron’s protection in return for the poet’s gift of the text—but Marot ultimately intends to bypass his patron and bestow a more profound gift upon the French people by way of this exchange, namely, to further a more evangelical scriptural approach and devotional practice.